2010
DOI: 10.1007/s11172-010-0168-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and spectral kinetic study of photoinduced processes of photochromic nitro-substituted indoline and benzothienopyrroline spiropyrans in solutions

Abstract: Nitro substituted benzothienopyrroline spiropyrans containing substituents in the ben zothienopyrroline moiety were synthesized. The comparative spectral kinetic study of the pho tochromic transformations of these compounds and their indoline analogs in solvents of various polarity was carried out. On the basis of the results obtained and literature data, the photoin duced aggregation of molecules of the merocyanine form in weakly polar solvents was sug gested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…To attain this goal, we decided to focus on the spiro-pyran molecular switch, whose UV-induced form (i.e., merocyanine; MC) is significantly more polar than cis-azobenzene, which should trigger a rapid back-isomerization reaction. Our initial experiments with model compounds confirmed this reasoning: we found that whereas the cis form of a simple azobenzene decayed with a first-order rate constant of k ≈ 0.41 day −1 , the open-ring isomer of the parent spiropyran isomerized with k ≈ 0.13 s −1 (in agreement with previous reports 35 )i.e., over four orders of magnitude faster (see the ESI, section 2 †). Recently, we developed the synthesis of spiropyran-functionalized Au 25 nanoclusters and noted a rapid (within 10 minutes) dark disassembly of UV-generated aggregates of these nanoclusters.…”
Section: Introductionsupporting
confidence: 90%
“…To attain this goal, we decided to focus on the spiro-pyran molecular switch, whose UV-induced form (i.e., merocyanine; MC) is significantly more polar than cis-azobenzene, which should trigger a rapid back-isomerization reaction. Our initial experiments with model compounds confirmed this reasoning: we found that whereas the cis form of a simple azobenzene decayed with a first-order rate constant of k ≈ 0.41 day −1 , the open-ring isomer of the parent spiropyran isomerized with k ≈ 0.13 s −1 (in agreement with previous reports 35 )i.e., over four orders of magnitude faster (see the ESI, section 2 †). Recently, we developed the synthesis of spiropyran-functionalized Au 25 nanoclusters and noted a rapid (within 10 minutes) dark disassembly of UV-generated aggregates of these nanoclusters.…”
Section: Introductionsupporting
confidence: 90%
“…53 In solution, the decay rate of the thermally unstable MC-form depends on the solvent polarity. For example, in polar solvents, the thermal conversion of 1′,3′-dihydro-1′,3′-3′-trimethyl-6-nitrospiro[2H]-1-benzopyran-2′,2′-(2H)-indole] (6-nitro-BIPS) tends to have slower rates than in less polar solvents, (i.e., 4.28 × 10 −5 s −1 in ethanol, 54 compared to 5 × 10 −2 s −1 in toluene 55 ). The rate of decay of the MC-form in the SP-LA SAM in this study is on the same time scale as the relaxation of spiropyran when present in polar solvents.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…10 shows the integrated intensities of the c-BTFO4 and MC emission bands obtained from periodic excitation after UV irradiation. The thermal relaxation lifetime of MC is B5.7 h, much longer than observed in various liquid solvents (B10-1800 s), [63][64][65] due to PMMA hindering photoisomerization. It is important to remember that recording the P1 + P3 film's fluorescence also causes c-BTFO4 to photoisomerize back to o-BTFO4, which slowly reduces the former's emission intensity with repeated sampling.…”
Section: P1 + P3 Pmma Filmmentioning
confidence: 80%